Il doppio materno: Pirandellian motherhood revisited - Čale-Feldman, Lada (2004)
In contrast to the prevailing stance in criticism regarding Pirandello's patriarchal treatment of one of his frequent topics, motherhood, this analysis of his play "La vita che ti diedi" insists on deconstructive and metadramatic effects produced by the confrontation of various maternal doubles governing the dramaturgy of the play.
Projekt MZOS
ENG